PARTISIPASI MASYARAKAT TENTANG FUNGSI HUTAN DI KENAGARIAN SUNGAI BETUNG KECAMATAN KAMANG BARU KABUPATEN SIJUNJUNG - Oka Rafiola, Yance; Ahmad, Drs. Ridwan; Yuherman, SP., M.Pd, Yuherman, SP., M.Pd (Pendidikan Geografi, 2014)
ABSTRACKÂ This study aims to determine the Peoples Participation On Kenagarian River Forest Function in Betong District of New Kamang Sijunjung district .This research is qualitative . A qualitative approach is the process of research and understanding based on the methodology menyelididki a social phenomenon and human issues . In this approach , researchers have emphasized Socially constructed reality , the close relationship between researcher and subject diteliti.Metodologi in this study is the people who live around the forest fringe villages Betong River .The results of the study found that : 1 ) the low public knowledge about the function of Betong River Forest , then sued the government in disseminating to the public over the River Betong . 2 ) community Betong River showed a fairly good attitude towards the forest , and river communities Betong in the present study aims to determine the Peoples Participation On Kenagarian River Forest Function in Betong District of New Kamang Sijunjung district .This research is qualitative . A qualitative approach is the process of research and understanding based on the methodology menyelididki a social phenomenon and human issues . In this approach , researchers have emphasized Socially constructed reality , the close relationship between researcher and subject diteliti.Metodologi in this study is the people who live around the forest fringe villages Betong River .The results of the study found that : 1 ) the low public knowledge about the function of Betong River Forest , then sued the government in disseminating to the public over the River Betong . 2 ) community Betong River showed a fairly good attitude towards the forest , and it has begun to membenah themselves in terms of their attitudes towards the forest and they begin to develop forests in Betong kenagarian River by planting rubber . 3 ) Betong River community show action on forest functions quite well , one of them with a rubber plant . And that in limiting the amount of plantation and land clearing for plantation forests in order to pay attention to forest ecosystem function properly maintained .